Accuracy of residential water meters in response to short, intermittent flows. Issue 1 (8th November 2018) - Chadwick, John R.; Barfuss, Steven L.; Johnson, Michael C.
Abstract : The purpose of this study was to measure the accuracy of residential water meters in response to short, intermittent flows. A gravimetric test bench was used as a standard to test 5/8″ × 3/4″ ultrasonic (US), electromagnetic (EM), nutating disc (ND), and oscillating piston (OP) meters. A programmable solenoid valve was used to create burst flow cycles. Three cycles of defined times were included in the study when the solenoid valve was open and closed and, subsequently, when water was flowing and not flowing—creating short, intermittent flows. Accuracies of water meters were tested at three flow rates: 4, 2, and 0.25 gpm. It was found that some of the US meters were affected by burst flows. EM meters were essentially unaffected by any burst flows. The accuracies of the ND and OP meters at the lowest flow tested were affected by burst flows.